2000
DOI: 10.1136/bjo.84.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase biology applied to vitreoretinal disorders

Abstract: Matrix metalloproteinases (MMPs) and their inhibitors are believed to have a significant role in a number of vitreoretinal diseases, from proliferative vitreoretinopathy to age related macular degeneration. The aim of this review is to summarise the current knowledge of their involvement in these diseases and to postulate potential therapeutic strategies.MMPs are a tightly regulated family of zinc dependent endopeptidases that are capable of degrading all components of the extracellular matrix (ECM) and baseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
47

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 135 publications
(109 reference statements)
1
51
0
47
Order By: Relevance
“…Another factor that potentially regulates the cleavage of FasL is the presence of tissue inhibitors of MMPs (TIMP), which are expressed within the eye and are the major endogenous regulators of MMP activity (24,32,33). Taken together with the data presented herein, we propose that the cleaving of FasL from the cell surface of tumor cells plays a critical role in the development of metastases.…”
Section: Discussionmentioning
confidence: 52%
“…Another factor that potentially regulates the cleavage of FasL is the presence of tissue inhibitors of MMPs (TIMP), which are expressed within the eye and are the major endogenous regulators of MMP activity (24,32,33). Taken together with the data presented herein, we propose that the cleaving of FasL from the cell surface of tumor cells plays a critical role in the development of metastases.…”
Section: Discussionmentioning
confidence: 52%
“…TIMPs are endogenous inhibitors of MMPs, which have an important role in connective tissue remodelling and in the degradation of the basal lamina and surrounding ECM during angiogenesis (Sethi et al 2000). Matrix remodeling, necessary for sprouting angiogenesis, is dependent on well-coordinated interactions between MMPs and TIMPs.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that, whatever the stimuli, the process of proteolysis by MMPs is an important step in the final common pathway of angiogenesis. Therefore, inhibition of the process of CNV at this level may be an attractive field of research rather than targeting the inciting stimuli themselves, which include many cytokines and other factors (19). Indeed it has recently been shown that there is reduced CNV in MMP-9 deficient mice (20).…”
Section: Introductionmentioning
confidence: 99%